Public re-release of going-concern opinions and market reaction. Issue 3 (16th April 2017) - Khan, Sarfraz A.; Lobo, Gerald; Nwaeze, Emeka T.
Abstract : This paper examines the market reaction to the public announcement of going-concern (GC) opinions through the news media. In the early 2000s, NASDAQ and AMEX required firms listed on their exchanges to publicly announce previously disclosed information, such as the issuance of a GC opinion, through a press release or the news media. We examine the stock market reaction to the re-release of GC opinions. We find significant abnormal stock return volatility and trading volume at the re-release of this information. Further, based on an analysis of intraday transactions, we find higher abnormal trading activity in small trades around the re-release of the GC opinion, but largely no changes in large trades during the same period. In this respect, the investors that initiate the small trades act as if they are surprised by the information contained in the press release of GC opinions. Such an action, in turn, can be viewed as evidence of a delayed response to the information in GC opinions by a section of investors.